2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26417
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study Investigating How First-Year Engineering Students' Value Beliefs Influence their Choice of Selecting an Engineering Major

Abstract: Raised in South Florida, born in Mexico. Half Colombian and half Mexican; proud Mexilombian. Héctor has an MS in Electrical and Computer Engineering and is currently pursuing a PhD in Engineering Education, both from Purdue University. His research interests include investigating LGBTQIA+ engineering student perception's of the culture of engineering. He's an avid videographer, eater of tasty food, moped enthusiast, and user/tweaker of computers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…This study also affirms prior research findings that, among other reasons, students select engineering because it promises practical utility and financial stability (Ortega-Alvarez, Atiqu, Rodriguez-Simmonds, 2016) that will allow them to provide for their families. And, while literature on Latino men often highlights a cultural and gender-motivated need to become financial providers (Saenz, Mercedes, Rodriguez, & Garcia Louis, 2017), this study demonstrates that Latina students in engineering may also feel that often masculine-attributed desire, perhaps as a result of their positioning within a male-dominated, potentially high-earning field.…”
Section: Discussionsupporting
confidence: 86%
“…This study also affirms prior research findings that, among other reasons, students select engineering because it promises practical utility and financial stability (Ortega-Alvarez, Atiqu, Rodriguez-Simmonds, 2016) that will allow them to provide for their families. And, while literature on Latino men often highlights a cultural and gender-motivated need to become financial providers (Saenz, Mercedes, Rodriguez, & Garcia Louis, 2017), this study demonstrates that Latina students in engineering may also feel that often masculine-attributed desire, perhaps as a result of their positioning within a male-dominated, potentially high-earning field.…”
Section: Discussionsupporting
confidence: 86%
“…Others have investigated what factors influence students' choices of major [6,13,26] . For example, Ortega-Alvarez and others examined engineering students' values [19] .They coded interview transcripts and survey responses into codes for value, competence, and expectation (categories for expectancy-value theory). Most reasons fell into one of these categories, but they found that family and being well informed about career choice were additional reasons not explained by the theory.…”
Section: Major Selectionmentioning
confidence: 99%